Adopting the Dutch Education System: Innovations to Improve the Quality of Education in Indonesia - Frizzy, Azriel Delmiro; Jingganingsandya, Hardiva Aura (Proceedings International Conference on Education Innovation and Social Science, 2024)
The study explores the potential of adopting elements of the Netherlands education system to enhance the quality of education in Indonesia. Given the longstanding historical and educational ties between the two countries, this research identifies key innovations from the Dutch system that could be adapted to the Indonesian context. The study examines differences in vocational education, teacher training, and student performance. The methodology involves a descriptive analysis of educational data from both countries, supported by qualitative insights from literature review regarding the issues raised. Results reveal that the Netherlands approach to a strong vocational training, and continuous teacher development leads to higher student satisfaction and academic achievement. These findings suggest several actionable strategies for Indonesia, such as strengthening ties with industries for vocational programs, and enhancing teacher training initiatives. Implementing these recommendations could significantly improve Indonesia's educational outcomes and global competitiveness. The study contributes to the ongoing discourse on educational reform by highlighting practical innovations that can be customized to address local needs and challenges in Indonesia.